Multi-element analysis in aerials parts of Verbena minutiflora and infusions - Kelly Cristina Nogueira Soares; Karlos Eduardo Pianoski; Daiane Finger; Yohandra Reyes Torres; Sueli Pércio Quináia (Universidade Estadual de Maringá, 2018)
This study evaluated the mineral content in the infusions and aerial parts (leaves, flowers and stems) of Gervão (Verbena minutiflora) for four consecutive years using the atomic spectrometry. The different parts of air V. minutiflora showed significant variability between certain mineral levels. The leaves and flowers showed the highest concentrations of all minerals, except for K, regardless of year of collection: stem (Fe = 50; Ca = 20, Zn = 770; Mg = 7.5; Cu = 4450; Al = 110; Na = 350, K = 13520 mg kg-1), flowers (Fe = 150, Ca = 33, Zn = 1.110, mg = 15, Cu = 7510, Al = 480; Na = 260, K = 10620 mg kg-1), leaves (Fe = 340, Ca = 35; 1930 = Zn, mg = 20, Cu = 12600; Al = 1.160; Na = 420, K = 12180 mg Kg-1). Notably, the concentrations of toxic elements (Pb, Cd and Cr) were below the limits of detection and quantification of the analytical technique in any shoot of Verbena. Minerals determined in aqueous infusions showed proportions ranging from 1.7 to 57.1% of the total value of minerals found in the leaves of Verbena.